Management of postpartum haemorrhage: from research into practice, a narrative review of the literature and the Cardiff experience. (February 2019) - Collins, P.W.; Bell, S.F.; de Lloyd, L.; Collis, R.E.
Highlights: Fibrinogen falls before other coagulation factors during postpartum haemorrhage (PPH). Laboratory Clauss fibrinogen and point-of-care FIBTEM A5 predict progression of PPH. Haemostatic impairment is uncommon during PPH and can be assessed by FIBTEM. A fibrinogen of 2 g/L or FIBTEM A5 12 mm and above is adequate for haemostasis during PPH. A national quality improvement programme has been initiated integrating these results. Abstract: Postpartum haemorrhage (PPH) is caused by obstetric complications but may be exacerbated by haemostatic impairment. In a 10-year programme of research we have established that haemostatic impairment is uncommon in moderate PPH and that fibrinogen falls earlier than other coagulation factors. Laboratory Clauss fibrinogen and the point-of-care surrogate measure of fibrinogen (FIBTEM A5 measured on the ROTEM® machine) are predictive biomarkers for progression from early to severe PPH, the need for blood transfusion and invasive procedures to control haemorrhage. Fibrinogen replacement is not required in PPH unless the plasma level falls below 2 g/L or the FIBTEM A5 is below 12 mm. Deficiencies of coagulation factors other than fibrinogen are uncommon even during severe PPH, and ROTEM® monitoring can inform withholding FFP safely in most women. In the absence of placental abruption, clinically significant thrombocytopenia is uncommon unless the platelet count is low before the bleed started, or very large bleeds (>5000 mL) occur. Measuring blood loss is feasible in routine practice during PPH and is more accurate than estimation. These research findings have been collated to design an ongoing quality improvement programme for all maternity units in Wales called OBS Cymru (Wales) (The Obstetric Bleeding Strategy for Wales).